Antibacterial Activity of Senna italica Extracts Against Multidrug-Resistant Pathogenic Isolates Associated with Otitis Media - Ahmed Almahdi; Shamsi Shamsi; Abdlrhman Alsonosi (AlQalam Journal of Medical and Applied Sciences, 2025)
The increasing prevalence of antibiotic-resistant bacterial strains poses a significant public health challenge, particularly in the treatment of infections such as otitis media. This study investigated the antibacterial potential of Senna italica spp. extracts against bacterial isolates from otitis media cases. Extracts were prepared using ethanol, water, acetone, and chloroform and tested against Staphylococcus aureus, Pseudomonas spp., Streptococcus spp., Escherichia coli, and Klebsiella spp. using disc diffusion and microdilution assays. The ethanol extract exhibited the most substantial antibacterial activity, with inhibition zones of up to 17 mm for Staphylococcus aureus and MIC values as low as 550 mg/mL against Streptococcus spp. Chloroform extracts demonstrated notable activity against Pseudomonas spp., with an MIC of 280 mg/mL. Water extracts did not exhibit any antibacterial effects. Among the antibiotics, Gentamicin and Ciprofloxacin demonstrated the highest efficacy, achieving inhibition zones of 22 mm across all tested isolates. In contrast, resistance to Cefoxitin and Amoxicillin/Clavulanic Acid was observed in 100% and 86% of isolates, respectively. This study highlights the potential of Senna italica spp. as a source of natural antibacterial agents, particularly against gram-positive bacteria such as Staphylococcus aureus and Streptococcus spp., and underscores the importance of solvent selection in optimizing extract efficacy. Although less effective than conventional antibiotics, these findings suggest that plant-based extracts could serve as complementary therapies to address antibiotic resistance. Future studies should focus on isolating bioactive compounds, evaluating their safety profiles, and exploring their synergistic effects with existing antibiotics. These findings contribute to the growing evidence supporting the role of medicinal plants in the development of alternative antimicrobial strategies.